Smoking Cessation after Bladder Cancer Diagnosis - Mota, Paulo (2018)
Introduction: Smoking is an important risk factor for the development, recurrence and progression of bladder cancer. Our aim was to analyze smoking habits after diagnosis in bladder cancer patients. Additionally, we evaluated patient knowledge about smoking as a risk factor and the urologist role in promoting abstinence.Material and Methods: A cross-sectional, observational and descriptive study was performed in bladder cancer patients, diagnosed between January 2013 and September 2015 (n = 160) in Braga Hospital, in Portugal.Results: Smoking history was present in 71.9% of the sample, with 21.9% current smokers, (40.7% of abstinence after diagnosis). Smoking was acknowledged as a risk factor by 74.4% of the sample, with only 51.3% of ever smokers and 24.4% of non-smokers recognizing smoking as the leading risk factor (p = 0.008). The presence of other household smokers were significantly higher in patients who continued smoking (40%) than in ex-smokers after diagnosis (4.2%) (p = 0.005). The majority of smokers at diagnosis (83.1%) were advised to quit by their urologist, but only one smoker (1.7%) was offered any specific intervention to aid in cessation.Discussion: Smoking is not recognized as the leading risk factor for bladder cancer. This limited awareness, associated with the known difficulties in quitting smoking and the observed lack of smoking cessation interventions, may account for the high current smoking prevalence, albeit in line with other studies.Conclusion: This study highlights the need for efficient smoking cessation programs directed to bladder cancer patients.